Severe Deficit in Energy and Protein Intake Correlates wih Stunting among Children Aged 12-24 Months in Plerean Sumberjambe Jember - Nunung Nurhasanah; Dwita Aryadina Rachmawati; Ika Rahmawati Sutejo (Faculty of Medicine, University of Jember, 2021)
The current nutritional problems are still the world's attention, especially in developing countries, including Indonesia. The Global Nutrition Report shows that Indonesia is a country with three main nutritional problems: wasting, overweight, and stunting (under five) in infants. Stunting has short-term and long-term effects associated with growth and developmental disorders. This study wants to determine the correlation between energy and protein intake of children aged 12-24 months in Plerean, Sumberjambe, Jember. This is an observational research with cross sectional study design. The population of this study were all children aged 12-24 months in Plerean Village, Sumberjambe, Jember. A total of 48 parents/respondents were interviewed about the consumption history of the on the previous day. This is done to determine the energy and protein intake consumed by the research subjects. Measurement of energy and protein intake using 24-hours food recall method and stunting was obtained from secondary data obtained from Puskesmas Sumberjambe. This research used purposive sampling method. The data obtained is then converted into calorie units and processed using a statistical program. The results showed showed 28 subjects were male. Most parents of research subjects earn less than the Minimum Wage District (UMK). A total of 68.75% of subjects had severe deficit in energy intake. A total of 52.08% of subjects had a severe deficit protein. Using Spearman correlation test the correlation of energy intake with the incidence of stunting obtained p value = 0.000 with correlation coefficient -0.589. Then, the relationship of protein intake with the incidence of stunting obtained p = 0.001 with a correlation coefficient of -0.446. So it can be concluded that severe deficit in energy and protein intake correlates with stunting in the study subjects. Keywords: 24-hours food recall, Energy, Protein, Stunting